PVDF / APP nano-microsphere flame-retardant composite membrane as well as preparation method and application thereof
By using PVDF/APP nano-microsphere flame retardant composite membrane in the battery separator, the problem of difficult to balance flame retardant performance and electrochemical performance in the prior art is solved, efficient flame retardant and good electrochemical performance are achieved, and the safety and performance of lithium-ion batteries are significantly improved.
Patent Information
- Application Number
- CN202411957683.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2044-12-30
AI Technical Summary
Existing battery separators are difficult to balance between flame retardant properties and electrochemical properties, resulting in the risk of combustion and explosion of lithium-ion batteries when thermally runaway, and at the same time, the electrochemical performance is poor.
The PVDF/APP nano-microsphere flame retardant composite membrane was used to convert ammonium polyphosphate from a large-size block to a small-size sphere through hydrolysis reaction, which improved its dispersion and compatibility, and was evenly distributed in the PVDF porous membrane.
It significantly improves the flame retardant and electrochemical properties of the battery separator, reduces the combustion risk during thermal runaway, extends battery life, and improves thermal management and use reliability.
Smart Images

Figure CN119955134A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of battery separator materials, and in particular to a PVDF / APP nano-microsphere flame-retardant composite film and a preparation method and application thereof. Background Art
[0002] With the rise of electric vehicles and renewable energy storage systems, the demand for lithium-ion batteries has increased significantly. At present, battery safety has become an important consideration in design and application. Thermal runaway, fire and explosion incidents of lithium-ion batteries have aroused widespread concern, so it is particularly important to develop high-safety and flame-retardant battery separators. Battery separators are an important component of lithium-ion batteries, playing the functions of ion conduction, mechanical support and thermal management. Lithium-ion batteries may experience thermal runaway under high temperature, overcharge or physical damage, causing the temperature inside the battery to rise sharply, which will cause the decomposition of the electrolyte and the reaction of the electrode materials and trigger more serious chemical reactions, leading to combustion or even explosion. Therefore, battery separators with excellent flame retardant properties can delay or even prevent the occurrence and further spread of fire after the battery has thermal runaway.
[0003] In the current preparation of flame-retardant battery separators, coating technology and composite material technology are two important technical means. The characteristics of coating technology are: first, the flame retardant and the binder are evenly mixed to prepare the coating material, and then the coating material is applied to the surface of the commercial polyethylene (PE) or polypropylene (PP) separator by scraping or spraying to achieve the preparation of flame-retardant separator materials. Although coating technology can improve the flame retardancy of the separator, it is affected by the stability and bulk density of the coating itself, which will lead to problems such as decreased ion conductivity of the separator, increased thickness, increased electrolyte viscosity, and increased side reactions, which ultimately lead to poor battery performance and decreased energy density. Composite material technology is to compound the flame retardant with the polymer substrate through melt extrusion, phase inversion and other methods to obtain good flame retardant properties, but this technology is limited by the type of battery separator material or the composite method. Composite material technology often has defects such as poor dispersion of flame retardants and large addition amount, which leads to increased costs and difficulty in large-scale industrial production.
[0004] Ammonium polyphosphate (APP) is a common phosphorus-based inorganic flame retardant, which has the remarkable characteristics of strong hygroscopicity, easy precipitation, and hydrolysis reaction at a certain temperature and in the presence of water. Therefore, researchers usually consider surface modification to protect it in order to prepare a composite flame retardant with good performance, such as: Patent CN111349355A uses silane coupling agent to modify the surface of ammonium polyphosphate, and then hexagonal boron nitride is grafted on the surface of ammonium polyphosphate to improve the thermal stability and water resistance of ammonium polyphosphate; Patent CN112011093A designs a multilayer core-shell structure composite material, which adsorbs chitosan and phytic acid on the surface of ammonium polyphosphate particles through opposite charge electrostatic flocculation to reduce the hydrophilicity of ammonium polyphosphate. However, due to the fact that the APP raw material itself is a micron-sized bulk particle, the high flame retardant performance of the composite battery separator filled with APP requires a high filling amount of APP, which will cause damage to the diaphragm pore structure and increase the internal resistance of the diaphragm, which seriously restricts the performance of the battery's electrochemical performance.
[0005] Therefore, it is urgent to develop a new battery separator to effectively exert the flame retardant properties of APP and reduce the need for high APP addition. Summary of the invention
[0006] In view of this, the present invention proposes a PVDF / APP nano-microsphere flame-retardant composite film capable of balancing the relationship between the amount of APP added and battery performance, as well as a preparation method and application thereof.
[0007] In a first aspect, the present invention provides a PVDF / APP nano-microsphere flame-retardant composite film, wherein the PVDF / APP nano-microsphere flame-retardant composite film comprises a polymer PVDF and a flame retardant APP, wherein the flame retardant APP accounts for at most 10% of the mass of the polymer PVDF.
[0008] Furthermore, the average pore size of the PVDF / APP nanosphere flame retardant composite membrane is 50-250 nm, and the size of the flame retardant APP is 100-200 nm.
[0009] In a second aspect, the present invention provides a method for preparing the above-mentioned PVDF / APP nanosphere flame retardant composite film, the method comprising the following steps:
[0010] S1. Dissolve PVDF powder and APP powder in N,N-dimethylformamide (DMF) solvent, stir at room temperature to obtain a casting solution;
[0011] S2, spreading the casting solution of step S1 on the surface of the coagulation bath solution to obtain a wet PVDF / APP composite membrane;
[0012] S3, transferring the PVDF / APP composite membrane of step S2 onto a flat inorganic glass substrate and laying it flat;
[0013] S4, dripping the coagulation bath solution of step S2 onto the surface of the PVDF / APP composite membrane treated in step S3 to keep the PVDF / APP composite membrane in a wet state;
[0014] S5, taking another flat inorganic glass substrate, completely fitting and covering the surface of the PVDF / APP composite film treated in step S4, and fully wrapping the upper and lower glass substrates and the PVDF / APP composite film sandwiched in the middle with plastic wrap;
[0015] S6, drying and heat-insulating the package of step S5;
[0016] S7, opening the package treated in step S6, taking out the PVDF / APP composite membrane sandwiched between the two glass substrates, and washing it three times with pure water, and air-drying it naturally to obtain a PVDF / APP nanosphere composite membrane.
[0017] Since ammonium polyphosphate will undergo hydrolysis reaction at a certain temperature and in the presence of moisture, in flame retardant and related fields, hydrolysis reaction is often avoided to prevent product performance from being affected. However, the present application makes full use of the characteristic that ammonium polyphosphate is easy to absorb water and hydrolyze. When preparing the composite film of the present application based on the film-making method in the invention patent CN118126373A or the invention patent CN116751382A, the ammonium polyphosphate is fully exposed to a certain temperature and water condition to promote its full hydrolysis, so that the particle size of the ammonium polyphosphate is reduced from the initial 20-30μm to 100-200nm, and a regular spherical structure is formed, which significantly improves its dispersibility and compatibility with the polymer (PVDF), and reduces the addition amount to less than 20%, significantly improving the flame retardant efficiency and reducing its influence on the structure of the film itself, so that the composite film can be used as a flame retardant battery separator with excellent performance in the battery field.
[0018] Furthermore, in step S1, the mass ratio of the PVDF powder to the DMF solvent is 1:(6.2-6.3).
[0019] Furthermore, in step S1, the stirring time is 45 to 48 hours.
[0020] Furthermore, in step S2, the coagulation bath solution is prepared by mixing DMF solvent and water; in terms of volume percentage, the volume ratio of the DMF solvent to the water is 60-70:40-30.
[0021] Furthermore, in step S4, the amount of the coagulation bath solution added is 2 Add 18-24 ml to the membrane surface.
[0022] By adopting the above technical solution, ammonium polyphosphate (APP) can be fully hydrolyzed in a wet state to form regular nanospheres, which helps to maintain the porous structure of the film and avoid cracks and uneven structures. In addition, the formation of nanospheres further improves the dispersibility and flame retardant efficiency of the flame retardant, and its uniform distribution in the polyvinylidene fluoride (PVDF) matrix also enhances the mechanical properties of the film.
[0023] Furthermore, in step S6, the drying and heat preservation temperature is 50-60° C. and the time is 18-20 hours.
[0024] By adopting the above technical solution, the film can be solidified to avoid deformation and shrinkage caused by long-term exposure to the air, so as to form a stable structure. At the same time, drying and heat preservation help evaporate the water in the film, thereby forming a dense and uniform film structure and improving the mechanical strength and toughness of the film. After drying and heat preservation, the physical properties of the film are more stable.
[0025] Furthermore, in step S7, the natural air drying is performed for 60 to 90 minutes.
[0026] Furthermore, the invention also includes application of the PVDF / APP nanosphere flame retardant composite film in lithium batteries.
[0027] By adopting the above technical scheme, when the PVDF / APP nanosphere flame retardant composite film of the present invention is used as a separator material for lithium batteries, the APP in the form of nanospheres has a high specific surface area and can be evenly dispersed in the PVDF matrix, thereby significantly improving the flame retardant performance. When the battery undergoes thermal runaway, the nanospheres can quickly decompose to form acidic substances such as polyphosphoric acid and metaphosphoric acid, promote the carbonization of PVDF, and form a dense carbonized layer to isolate combustibles and oxygen to delay or even prevent the combustion process. At the same time, the formation of nanospheres will not destroy the porous structure of the membrane, thereby enabling the battery separator material to maintain good air permeability and ion conductivity.
[0028] In the present invention, the peak heat release rate of the lithium battery equipped with the PVDF / APP nanosphere flame retardant composite film of the present invention is reduced by no more than 45%, and the total heat release amount is reduced by no more than 26%.
[0029] By adopting the above technical solution, the safety performance of lithium batteries in thermal runaway is significantly improved, the risk of combustion is reduced, the battery life is extended, and the reliability of thermal management and use is improved.
[0030] Compared with the prior art, the PVDF / APP nanosphere flame retardant composite film provided by the present invention has the following advantages:
[0031] Beneficial effects:
[0032] (1) The composite film provided by the present invention and its application in lithium battery separators can achieve a good flame retardant effect by controlling the addition amount of the flame retardant to less than 10%. Compared with the 40%-50% addition amount usually required in the prior art, the present invention not only significantly reduces the production cost, but also makes the composite film lighter.
[0033] (2) In the battery separators existing in the prior art, the particle size of phosphorus-based flame retardants is not less than 0.6 μm, and most of them are irregular block structures, which easily lead to the destruction of the structure of the film itself and reduce the porosity and air permeability. Compared with the prior art, the size of the flame retardant in the composite film involved in the present invention is 100-200 nm, and the shape is a uniform sphere, which has a higher specific surface area and better compatibility.
[0034] (3) The peak heat release rate of the soft-pack battery assembled with the flame-retardant diaphragm in the prior art is reduced by no more than 30%, and the total heat release is no more than 20%. The peak heat release rate of the soft-pack battery assembled with the composite membrane involved in the present invention is reduced by up to 45%, and the total heat release is reduced by up to 26%. Compared with the flame-retardant diaphragm in the prior art, the composite membrane involved in the present invention has better flame retardant properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0036] Figure 1 The transmission electron microscope images are of the hydrolysis process of ammonium polyphosphate in the coagulation bath solution at different time periods according to Example 1 of the present invention;
[0037] In the figure, a is a transmission electron micrograph of ammonium polyphosphate without any treatment, b is a transmission electron micrograph of ammonium polyphosphate after hydrolysis for 10 hours, c is a transmission electron micrograph of ammonium polyphosphate after hydrolysis for 15 hours, and d is a transmission electron micrograph of ammonium polyphosphate after hydrolysis for 20 hours;
[0038] Figure 2 This is a scanning electron microscope (SEM) image of the PVDF / APP nanosphere flame retardant composite film prepared in Example 1 of the present invention;
[0039] In the figure, a is a surface electron microscope scanning SEM image of the PVDF / APP nano-microsphere flame retardant composite film prepared in Example 1, and b is a cross-sectional electron microscope scanning SEM image of the PVDF / APP nano-microsphere flame retardant composite film prepared in Example 1;
[0040] Figure 3 This is a combustion photo of the PVDF / APP nanosphere flame retardant composite film prepared in Example 1 of the present invention;
[0041] Figure 4 This is a scanning electron microscope (SEM) image of the PVDF / APP nanosphere flame retardant composite film prepared in Example 1 of the present invention;
[0042] In the figure, a is a scanning electron microscope SEM image of the PVDF / APP nano-microsphere flame retardant composite film at the initial combustion, and b is a scanning electron microscope SEM image of the PVDF / APP nano-microsphere flame retardant composite film after combustion;
[0043] Figure 5 This is a combustion photo of the PVDF / APP composite membrane prepared in Comparative Example 1 of the present invention;
[0044] Figure 6 This is a scanning electron microscope (SEM) image of the PVDF / APP composite membrane prepared in Comparative Example 1 of the present invention;
[0045] In the figure, a is a SEM image of the PVDF / APP composite membrane at the time of initial combustion, and b is a SEM image of the PVDF / APP composite membrane after combustion;
[0046] Figure 7 This is a heat release rate diagram of the soft-pack battery assembled from Comparative Example 1 and Example 1 during combustion of the present invention;
[0047] In the figure, a is a heat release rate diagram of the soft-pack battery assembled with the PVDF / APP composite film prepared in Comparative Example 1 during combustion, and b is a heat release rate diagram of the soft-pack battery assembled with the PVDF / APP nanosphere flame-retardant composite film prepared in Example 1 during combustion;
[0048] Figure 8 This is a graph of total heat release when the soft-pack battery assembled from Comparative Example 1 and Example 1 of the present invention is burned;
[0049] In the figure, a is a graph of the total heat release of the soft-pack battery assembled with the PVDF / APP composite film prepared in Comparative Example 1 during combustion, and b is a graph of the total heat release of the soft-pack battery assembled with the PVDF / APP nanosphere flame-retardant composite film prepared in Example 1 during combustion;
[0050] Fig. 9 The heat resistance test photos of the PVDF / APP nano-microsphere composite film prepared in Example 1 of the present invention and the commercial PP film;
[0051] Fig.10 This is a cycle performance diagram of a button cell assembled with a PVDF / APP composite membrane prepared in a comparative example of the present invention at room temperature;
[0052] Fig.11 This is a cycle performance diagram of a button cell assembled with the PVDF / APP nanosphere flame-retardant composite film prepared in Example 1 of the present invention at room temperature. DETAILED DESCRIPTION
[0053] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0054] The present invention is further described below in conjunction with specific examples, and the protection scope of the present invention is not limited by the following examples. The materials mainly involved in the examples and comparative examples are conventional commercial products unless otherwise specified.
[0055] Ammonium polyphosphate 20~30μm CAS McLean
[0056] Example 1
[0057] The PVDF / APP nanosphere flame retardant composite film of this embodiment is prepared by the following steps, including:
[0058] S1. 13.5 g of PVDF powder and 2.7 g of APP raw material powder were put into 83.8 g of DMF solvent and stirred at room temperature for 48 hours to obtain a casting solution;
[0059] S2. Spreading and curing the casting solution of step S1 on the surface of the coagulation bath solution to obtain a wet PVDF / APP composite membrane; wherein the volume ratio of DMF solvent to H2O in the coagulation bath solution is 65:35;
[0060] S3. The wet PVDF / APP composite film obtained in step S2 is transferred to a flat inorganic glass substrate and fully tiled;
[0061] S4. The surface of the wet PVDF / APP composite membrane fully laid in step S3 is per 100 cm 2 20 mL of the coagulation bath solution in step S2 was dripped onto the membrane surface to wet the PVDF / APP composite membrane;
[0062] S5. Take another flat inorganic glass substrate used in step S3, completely fit the surface of the PVDF / APP composite film covered in the fully tiled wet state in step S4, and fully wrap the upper and lower glass substrates and the composite film sandwiched in the middle with plastic wrap;
[0063] S6. The package in step S5 is placed in a blast drying oven and kept warm at 60°C for 20 hours;
[0064] S7. Open the package in step S6, take out the wet PVDF / APP composite membrane sandwiched between the glass substrates, soak and wash it three times with pure water, and then air-dry it at room temperature for 1 hour to obtain the final PVDF / APP nanosphere composite membrane.
[0065] The hydrolysis process of APP in this example at different time in the coagulation bath solution is as follows Figure 1 As shown in the figure, it can be seen that with the extension of time, the APP raw material gradually changes from micron-sized blocks to nano-sized microspheres.
[0066] The PVDF / APP nanosphere composite membrane prepared in this example was tested by scanning electron microscopy (SEM). Figure 2 As shown. Figure 2 It can be seen that APP nanospheres are evenly distributed on the surface and inside of the composite film.
[0067] The PVDF / APP nanosphere composite membrane prepared in this example was cut into strips of 8 mm*2 mm and ignited with a flame to observe the combustion of the composite membrane. The results are as follows: Figure 3 shown.
[0068] Depend on Figure 3 It can be seen that: thanks to the good dispersibility and compatibility of the nano-microsphere ammonium polyphosphate, the PVDF / APP nano-microsphere composite membrane of this embodiment exhibits good self-extinguishing property and good dimensional stability.
[0069] The PVDF / APP nanosphere composite membrane prepared in this example was subjected to scanning electron microscopy during initial combustion and after combustion. The results are as follows: Figure 4 shown.
[0070] Depend on Figure 4 It can be seen that: during the initial combustion, APP is in the form of nano-scale microspheres and is evenly distributed on the surface of the composite membrane, forming a dense structure of the composite membrane. After combustion, the APP nano-scale microspheres on the surface of the composite membrane disappear, and the surface becomes smooth, and the density is further improved. It can be seen from the illustration that after combustion, the structure of the composite membrane remains intact.
[0071] Comparative Example 1
[0072] The method for preparing the PVDF / APP composite membrane in this comparative example comprises the following steps:
[0073] S1. 13.5 g of PVDF powder and 2.7 g of APP raw material powder were put into 83.8 g of DMF solvent and stirred at room temperature for 48 hours to obtain a casting solution;
[0074] S2. Spread and solidify the casting solution of step S1 on the surface of the coagulation bath solution, and dry to obtain a PVDF / APP composite membrane; wherein the volume ratio of DMF solvent to H2O in the coagulation bath solution is 65:35.
[0075] The PVDF / APP composite membrane prepared in this comparative example was cut into strips of 8 mm*2 mm and ignited with a flame to observe the combustion of the composite membrane. The results are as follows: Figure 5 shown.
[0076] Depend on Figure 5 It can be seen that due to the large size and irregular shape of ammonium polyphosphate, the composite film in Comparative Example 1 showed obvious combustion phenomenon when encountering flame, showing poor flame retardant performance.
[0077] The PVDF / APP composite membrane prepared in this comparative example was subjected to scanning electron microscopy during initial combustion and after combustion. The results are as follows: Figure 6 shown.
[0078] Depend on Figure 6 It can be seen that the PVDF / APP composite membrane obtained by direct drying without the treatment of steps S3 to S7 of the present invention cannot have uniform distribution of APP micron-sized blocks during initial combustion, and after combustion, a loose, porous and incomplete structure is formed, that is, it becomes powder.
[0079] The PVDF / APP nanosphere flame retardant composite film prepared in the above Example 1 and the PVDF / APP composite film prepared in Comparative Example 1 were further used as lithium battery soft pack battery separator materials to test their heat release rate and total heat release. The test method specifically includes: using the PVDF / APP composite film to assemble a 100mm*100mm soft pack battery standard sample, placing the soft pack battery standard sample in a cone calorimeter model NK8115 of Dongguan Nayu Testing Equipment Co., Ltd., setting the power to 35kW and the oxygen content to 20%, collecting the heat release rate and total heat release of the sample during the test, and the test results are as follows: Figures 7-8 shown.
[0080] Depend on Figure 6 We can see that: compared with Comparative Example 1, the heat release rate of the soft-pack battery combustion test of the composite membrane prepared in Example 1 is lower, and its peak heat release rate is reduced by 45%, while the peak heat release rate of Comparative Example 1 is only reduced by 30%, indicating that the ammonium polyphosphate composite membrane after hydrolysis has better flame retardant effect.
[0081] Depend on Figure 7We can see that: compared with Comparative Example 1, the total heat release of the soft-pack battery combustion test of the composite diaphragm prepared in Example 1 is lower, and its total heat release is reduced by 26%, while the total heat release of Comparative Example 1 is reduced by less than 20%, indicating that the hydrolyzed ammonium polyphosphate composite diaphragm has a better flame retardant effect.
[0082] It can be seen from this that the PVDF / APP nano-microsphere flame-retardant composite film prepared by the present invention has good self-extinguishing properties, and compared with the membrane material not treated in steps S3 to S7, the decrease in peak heat release rate and total heat release in the soft-pack battery combustion test assembled with the composite film prepared by the present invention are increased by 50% and 30% respectively. Overall, the PVDF / APP nano-microsphere flame-retardant composite film prepared by the present invention has better flame retardant properties.
[0083] The PVDF / APP nanosphere flame retardant composite film prepared in Example 1 was subjected to a heat resistance test with a commercially available PP film (Celgard 2500, Suzhou Sinero Technology Co., Ltd.). The test results are shown in FIG. Fig. 9 shown.
[0084] Depend on Fig. 9 It can be seen that the heat resistance of the composite film prepared in the embodiment of the present invention is significantly better than that of the commercial PP film.
[0085] The PVDF / APP composite film prepared in Comparative Example 1 and the PVDF / APP nanosphere flame-retardant composite film prepared in Example 1 were assembled into a lithium battery Li||LFP button battery separator material, and the charge and discharge cycle performance of the button battery at room temperature was tested by the LANHE test system (LANHE) model CT3002A of Wuhan LANHE Electronics Co., Ltd. The test results are as follows: Figures 10-11 shown.
[0086] Fig.10 The figure is a cycle performance diagram of the button cell assembled with the PVDF / APP composite membrane prepared in Comparative Example 1 at room temperature. As can be seen from the figure, the battery capacity retention rate fluctuates significantly around 550 cycles, and the coulomb efficiency decreases significantly around 300 cycles.
[0087] Fig.11 The figure is a cycle performance diagram of a button cell assembled with the PVDF / APP nanosphere flame retardant composite film prepared in Example 1 at room temperature. It can be seen from the figure that the capacity retention rate of the cell after 750 cycles is 98%, and the coulombic efficiency is about 99%.
[0088] Combination Figures 10-11It can be concluded that the cycle stability of the battery assembled with the PVDF / APP nanosphere composite membrane prepared by the present invention can be improved by more than 130% (stable cycle number); and the battery capacity retention rate assembled with the PVDF / APP nanosphere composite membrane prepared by the present invention is improved by more than 100% when the flame retardant composite membrane is added in a higher amount; therefore, the PVDF / APP nanosphere composite membrane prepared by the present invention has better electrochemical properties.
[0089] In summary: the present invention successfully hydrolyzes ammonium polyphosphate from large-sized, irregular blocks into small-sized, regularly shaped spheres through a hydrolysis reaction, thereby improving its dispersibility and compatibility with the polymer matrix, and uniformly disperses it in a PVDF porous membrane to prepare a composite flame-retardant diaphragm. The actual assembly of soft-pack batteries and button batteries was used to conduct combustion tests and electrochemical performance tests, respectively, successfully verifying that it has both excellent flame retardant properties and good electrochemical properties.
[0090] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A PVDF / APP nanosphere flame retardant composite film, characterized in that: The PVDF / APP nano-microsphere flame-retardant composite film comprises polymer PVDF and flame retardant APP, wherein the flame retardant APP accounts for at most 10% of the mass of the polymer PVDF.
2. The PVDF / APP nanosphere flame retardant composite film according to claim 1, characterized in that: The average pore size of the PVDF / APP nanosphere flame-retardant composite membrane is 50-250 nm, and the size of the flame retardant APP is 100-200 nm.
3. A method for preparing the PVDF / APP nanosphere flame retardant composite film as claimed in claim 1 or 2, characterized in that: The method comprises the following steps: S1, dissolving PVDF powder and APP powder in DMF solvent, stirring at room temperature, to obtain a film casting solution; S2, spreading the casting solution of step S1 on the surface of the coagulation bath solution to obtain a wet PVDF / APP composite membrane; S3, transferring the PVDF / APP composite membrane of step S2 onto a flat inorganic glass substrate and laying it flat; S4, adding the coagulation bath solution of step S2 dropwise onto the surface of the PVDF / APP composite membrane treated in step S3; S5, taking another flat inorganic glass substrate, completely fitting and covering the surface of the PVDF / APP composite film treated in step S4, and fully wrapping the upper and lower glass substrates and the PVDF / APP composite film sandwiched in the middle with plastic wrap; S6, drying and heat-insulating the package of step S5; S7, opening the package treated in step S6, taking out the PVDF / APP composite membrane sandwiched between the two glass substrates, and soaking and washing it three times with pure water, and naturally air-drying it to obtain a PVDF / APP nano-microsphere composite membrane.
4. The method according to claim 3, characterized in that In step S1, the mass ratio of the PVDF powder to the DMF solvent is 1:(6.2-6.3).
5. The method according to claim 4, characterized in that The stirring time is 45 to 48 hours.
6. The method according to claim 3, characterized in that In step S2, the coagulation bath solution is prepared by mixing DMF solvent and water; in terms of volume percentage, the volume ratio of the DMF solvent to the water is 60-70:40-30.
7. The method according to claim 3, characterized in that In step S4, the amount of the coagulation bath solution added is 2 Add 18-24 ml to the membrane surface.
8. The method according to claim 3, characterized in that In step S6, the drying and heat preservation temperature is 50-60° C. and the time is 18-20 hours.
9. The method according to claim 3, characterized in that In step S7, the natural air drying is performed for 60 to 90 minutes.
10. Use of the PVDF / APP nanosphere flame retardant composite film as claimed in claim 1 or 2 in lithium batteries.
Citation Information
Patent Citations
Preparation method of polymer film
CN116751382A
Porous polymeric membrane and preparation method thereof
CN118126373A
Preparation method of ammonium polyphosphate microspheres
CN112430417A
Polyvinylidene fluoride coated micron aluminum composite powder and preparation method thereof
CN113683471A
Three-layer core-shell structure flame retardant, flame-retardant phase-change material, preparation method and application
CN116640581A
Cited By
Dual-network temperature-sensitive nano hydrogel for extinguishing fire and preventing after-combustion in lithium iron phosphate battery and preparation method of dual-network temperature-sensitive nano hydrogel
CN120665317A